Molecular analysis of the mating type (MAT1) locus in strains of the heterothallic ascomycete Botrytis cinerea. (7th March 2016) - De Miccolis Angelini, R. M.; Rotolo, C.; Pollastro, S.; Faretra, F.
Abstract : Botrytis cinerea shows a heterothallic bipolar mating‐type system; homothallism has been occasionally observed. MAT1 genes and flanking regions in the reference strains SAS56 ( MAT1‐1 ) and SAS405 ( MAT1‐2 ) and their monoascosporic progeny were analysed. The two mating types confirmed different sequences of 2513 bp ( MAT1‐1 ) and 2776 bp ( MAT1‐2 ), flanked by near identical regions. In all isolates, each idiomorph included two mating‐type specific genes: MAT1‐1‐1 (1161 bp), encoding an alpha‐domain containing protein, and MAT1‐1‐ 5 (1301 bp); or MAT1‐2‐1 (1236 bp), encoding a HMG‐domain protein, and MAT1‐2‐4 (712 bp); the latter genes encode putative proteins of unknown function. Truncated MAT1‐1‐1 (670 bp) and MAT1‐2‐1 (92 bp) sequences of the opposite mating‐type were found in the flanking regions. Idiomorph‐specific PCR primer pairs were used to explore the structure of the MAT1 locus in ascospore progeny and field isolates showing homothallic behaviour, and the locus organization in all of them did not differ from that of heterothallic strains. Constitutive expression of all the four mating‐type genes was ascertained by RT‐PCR at four different developmental stages (mycelium, sclerotia at two different stages and apothecia). Antisense transcription of the MAT1‐2‐1 gene with isoforms from alternative splicing was detected. Comparative analysis of MAT1 loci in B. cinerea and in the closely related homothallic Sclerotinia sclerotiorum led to the identification of short nearly identical sequences.